Reproductive Biology of Belontia hasselti Cuvier, 1831 from the Banjiran Swamp Air Hitam River, Payung Sekaki District, Riau Province - Adytia Eko Maulana; Ridwan Manda Putra; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTBelontia hasselti is commonly found in the Banjiran Swamp of the Air Hitam River. A study aims to understand the reproductive biology of B. hasselti has been conducted from February to March 2018. Fish sampling were conducted once / 2 weeks. Parameters measured were sex ratio, gonad maturity level, gonad somatic index (GSI), fecundity and egg diameter. Totally 100 fishes (46 males and 54 females) were captured, they were 70.8 – 130.05 mm TL and 7.44 – 41.59 gr BW. Male has slimmer body, darker body color than those of the female. Sex ratio of males and females was 1:1. In each sampling time there were  male fishes with 1st,2nd and 3rd maturity level, while the female fishes are in 1st ,2nd,3rd and 4th maturity levels. The GSI of male ranged from 0.20 – 1.14%, while that of the female is 0.75 – 28.94%. The fecundity is around 4,191 – 4,350 eggs/fish, and egg diameter was 0.8-1 mm.Keywords: Sex ratio, gonad maturity level, gonad somatic index, fecundity